2016
DOI: 10.1177/0040517516652350
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and in vitro cytotoxicity evaluation of alginate-AgNP fibers

Abstract: Biopolymer nanocomposites containing metal nanoparticles have attracted much attention due to their excellent properties and broad applications. In this work, alginate fibers embedded with silver nanoparticles (AgNPs) were prepared. The as-obtained alginate-AgNP fibers exhibited antibacterial activity against both Gram microorganisms of model microbes Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive). A growth kinetic study with S. aureus and E. coli displayed the inhibition of bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Antibacterial activity of alginate hydrogels against S. aureus and E. coli is confirmed in the literature [ 86 , 87 , 88 , 89 ] and is the result of the absence of free carbon in this material. The studies have shown that the presence of African plum bark extract in the hydrogel enhances the inhibitory effect of Gram-positive and Gram-negative bacteria.…”
Section: Resultssupporting
confidence: 68%
“…Antibacterial activity of alginate hydrogels against S. aureus and E. coli is confirmed in the literature [ 86 , 87 , 88 , 89 ] and is the result of the absence of free carbon in this material. The studies have shown that the presence of African plum bark extract in the hydrogel enhances the inhibitory effect of Gram-positive and Gram-negative bacteria.…”
Section: Resultssupporting
confidence: 68%
“…A typical TEM image of Ag/Alg film, as presented in Figure 3b, manifests that spherical AgNPs (the small black dots) are finely dispersed within Alg fibers [40]. When AgNO 3 was immersed in Alg solution, Ag + could easily diffuse into Alg fibers and reacted with the fibers via ion exchange with sodium ion in the fibers due to the negatively charged Alg facilitating the attraction of the positively charged Ag ions by electrostatic attraction [41]. Then, number of Ag + ions decreased in situ, and the formed AgNPs closely deposited in the Alg fibers.…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs can be combined with alginate to be used as a coating/finishing agent in fabrics or they can be incorporated into the alginate fiber itself in wet or electrospinning processes. For example, Zhao et al reported the wet spinning of alginate fibers embedded with AgNPs, where the antibacterial activity was proven efficient against both E. coli and S. aureus and had a high cell-killing efficiency in human cervical cancer (HeLa) cells [ 94 ]. Zhang et al also produced alginate nanofibers incorporated with Ag via electrospinning, where Ag was reduced in situ to obtain a highly sensitive humidity sensor able to monitor human breath [ 15 ].…”
Section: Polysaccharides In Metal-nanoparticle-functionalized Textilesmentioning
confidence: 99%